(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The effect of vertical throughflow and variable gravity field on the onset of penetrative convection simulated via internal heating in a porous medium is studied. Flow in the porous medium is governed by Forchheimer-extended Darcy equation. The boundaries are considered to be rigid, however permeable, and insulated to temperature perturbations. The eigen value problem is solved using a regular perturbation technique with wave number as a perturbation parameter. The variable gravity parameter, the direction of throughflow and the presence of volumetric internal heat source in a porous layer play a decisive role on the stability characteristics of the system. In addition, the influence of Prandtl number arising due to throughflow is also emphasized on the stability of the system. It is observed that both stabilizing and destabilizing factors can be enhanced due to the simultaneous presence of a volumetric source, gravity field and vertical throughflow so that a more precise control (suppress or augment) of thermal convective instability in a layer of porous medium is possible.